Development of a conditional gene knockout system to investigate the functional importance of regulatory genes in Plasmodium falciparum - Birkholtz, Lyn-Marie (University of Pretoria, 2024)
Dissertation (MSC (Biochemistry))--University of Pretoria, 2023.